2001
DOI: 10.1038/sj.ijo.0801802
|View full text |Cite
|
Sign up to set email alerts
|

Lack of heritability of circulating leptin concentration in humans after adjustment for body size and adiposity using a physiological approach

Abstract: OBJECTIVE:To construct a simple physiological model of leptin kinetics, based on measures of body size and composition, which is suitable for investigating the influence of genetic and other influences on circulating leptin levels in humans. METHODS: Consideration of the kinetics of the secretion and clearance of leptin led to a predicted linear relationship between ln(leptin), ln(fat mass), and a function of non-fat body compartments. Results obtained from this model were compared with those from two publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…This finding, as well as the heritability estimate for leptin (0.4670.11) was in good agreement with the corresponding estimates obtained in various other samples. 12,34,35,37,38 However, once we adjusted SBP in offspring for circulating leptin levels in parents, both parent-offspring correlation and h 2 estimates became not significantly different from zero. Thus, our findings propose that genetic variation in BMI, SKFs, and even body CRCs, as well as of SBP is due to genetic variation of leptin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding, as well as the heritability estimate for leptin (0.4670.11) was in good agreement with the corresponding estimates obtained in various other samples. 12,34,35,37,38 However, once we adjusted SBP in offspring for circulating leptin levels in parents, both parent-offspring correlation and h 2 estimates became not significantly different from zero. Thus, our findings propose that genetic variation in BMI, SKFs, and even body CRCs, as well as of SBP is due to genetic variation of leptin.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,34,35 Some of these studies estimated that BMI genetic variation is virtually indistinguishable from the genetic effects on leptin (eg 13 ), while others suggest the existence of both common and variable-specific genetic effects. 12,34,35 Moreover, it has been reported that one of the genetic polymorphisms strongly influencing genetic variation of BMI is reliably linked to a chromosomal area 7q33, very near to the location for the leptin gene. 36 Our present results confirm the conclusions with respect to genetic correlation between leptin and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Jenkins et al (Jenkins et al, 2001;Jenkins and Campbell, 2003) suggested that different associations among studies may be explained by differences in methods of adjustment for the variability in body composition. They argued that imperfect adjustments for baseline body fat are responsible for spurious positive association between baseline leptin and weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Using either BMI or percent body fat as covariates can lead to erroneous conclusions in a genetic context. 31 One possible approach is the use of multivariate phenotypic constructs obtained from techniques such …”
Section: Obesity Phenotypes Have Not Been Adequate In Most Genetic Anmentioning
confidence: 99%
“…The expected power benefits from multivariate phenotypes are most apparent when there are strong correlations between the individual phenotypes, as is the case with many phenotypes obtained in genomic studies of obesity, but this is not the only requirement for derivation of useful phenotypes. The aim must be to construct biologically informative phenotypes which, in principle, could be achieved either by applying prior knowledge to the development of explicit physiological models composed of measurable variables 31 or by careful consideration of the biological and statistical properties of the available raw phenotypes. 18 It is also important to consider the origins of the correlations between phenotypic markers, so as to specify the correct functional forms of the relationships, and especially to avoid correlated errors when choosing phenotypes for inclusion.…”
mentioning
confidence: 99%